Role of Perivascular Adipose Tissue and Exercise on Arterial Function with Obesity. Issue 3 (July 2021) - Boateng, Samuel Y.; Olfert, I. Mark; Chantler, Paul D.
Abstract : Adipose tissue and arterial dysfunction are common in the obese state. Perivascular adipose tissue (PVAT) plays an important role in mediating arterial health, and with obesity, the PVAT dysfunction negatively affects arterial health. Exercise training exerts direct and beneficial effects on PVAT, providing an additional and novel pathway by which exercise can improve arterial health in diseased populations. Abstract : Perivascular adipose tissue contributes to arterial dysfunction with obesity and exercise training can limit its role.